Cyclopamine functions as a suppressor of benign prostatic hyperplasia by inhibiting epithelial and stromal cell proliferation via suppression of the Hedgehog signaling pathway - Yuan, Yi-Feng (Int J Mol Med, 2020)
Stromal-epithelial interaction serves a pivotal role in normal prostate growth, as well as the onset of benign prostatic hyperplasia (BPH). The present study aimed to explore the role of cyclopamine in the proliferation and apoptosis of epithelial and stromal cells in rats with BPH by blocking the Hedgehog signaling pathway. Cyclopamine (an inhibitor of the Hedgehog signaling pathway) was administered in a rat model of BPH, and the expression of Ki67 (proliferation factor) was determined by immunohistochemistry. In addition, epithelial and stromal cells were separated and cultured in order to investigate the role of cyclopamine in the progression of BPH. The expression of Hedgehog signaling pathway- and apoptosis-related genes, including basic fibroblastic growth factor (b-FGF) and transforming growth factor β (TGF-β), was evaluated using reverse transcription-quantitative polymerase chain reaction and western blot analysis. Cell proliferation, cell cycle and apoptosis were analyzed using an MTT assay and flow cytometry. We identified upregulated Ki67 expression and activated Hedgehog signaling pathway in rats with BPH. Cyclopamine inhibited the activation of the Hedgehog signaling pathway. In response to cyclopamine treatment, epithelial and stromal cell proliferation was inhibited; this was concomitant with decreased Ki67, TGF-β, and b-FGF expression. On the other hand, epithelial cell apoptosis was enhanced, which was associated with increased Bax and reduced Bcl-2 expression. Based on these findings, we proposed that cyclopamine may serve as a potential therapeutic agent in the treatment of BPH. Cyclopamine could inhibit epithelial and stromal cell proliferation, and induce epithelial cell apoptosis by suppressing the Hedgehog signaling pathway.